Studi Etnobotani Jahe (Zingiber officinale) pada Masyarakat Desa Banyior Kecamatan Sepulu Kabupaten Bangkalan - Husnul Hotimah; Ari Hayati; Hasan Zayadi (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2019)
Ginger (Zingiber officinale) is a plant belonging to the Rhizoma group, ginger plants are relatively easy to find and its use has expanded not only for cooking purposes, but also for health, Ginger or commonly called